2017
DOI: 10.1371/journal.pone.0181766
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation in retinal vascular occlusion disease and non-arteritic anterior ischemic optic neuropathy

Abstract: BackgroundPatients with retinal vascular occlusion disease have an increased risk for ischemic stroke and share some risk factors with cerebrovascular disease. The purpose of this study was to analyze the prevalence of atrial fibrillation (AF) in subjects with retinal vascular occlusive disease and anterior ischemic optic neuropathy and to compare these data to an ischemic stroke group.MethodsProspective, observational single-center trial. Subjects with retinal artery occlusion (RAO), retinal vein occlusion (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 38 publications
2
26
0
6
Order By: Relevance
“…The association of AF and RAO is not investigated to the same extent as the association of AF and ischemic stroke. Whereas one study found a similar detection rate of AF in RAO patients AF (12.5% of patients using 24-h ECG (at least)), other studies indicate that AF is more common in patients with ischemic stroke and find a higher number needed to screen in patients with RAO than in patients with ischemic stroke [ 14 , 37 , 38 ]. Patients with AF have a higher ratio of hemispheric to retinal occlusions compared to patients with AF, which may indicate that other embolic sources than the atria such as a carotid stenosis play a larger role in RAO patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of AF and RAO is not investigated to the same extent as the association of AF and ischemic stroke. Whereas one study found a similar detection rate of AF in RAO patients AF (12.5% of patients using 24-h ECG (at least)), other studies indicate that AF is more common in patients with ischemic stroke and find a higher number needed to screen in patients with RAO than in patients with ischemic stroke [ 14 , 37 , 38 ]. Patients with AF have a higher ratio of hemispheric to retinal occlusions compared to patients with AF, which may indicate that other embolic sources than the atria such as a carotid stenosis play a larger role in RAO patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study substantiates the importance of a careful work-up required in patients with retinal vascular occlusion, which is in accordance with other studies. [ 37 , 45 ] Detection of AF leads to indication for oral anticoagulation (in the presence of at least one CHA 2 DS 2 -VASc point) to efficiently reduce risk of ischemic stroke. [ 46 , 47 ] Further studies are needed to estimate the effect of oral anticoagulation on the risk of RAO.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent ophthalmoscopic findings include retinal edema, attenuation or segmentation of retinal arterioles and visible retinal artery emboli [2]. Similar to ischemic stroke, CRAO is mainly caused by emboli originating from large artery atherosclerosis [3][4][5] or car-K dioembolism [6,7], although a wider etiologic spectrum needs to be considered [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…1). Die Untersuchung ist einfach durchführbar und sollte mittels hochfrequentem Linearschallkopf erfolgen (7)(8)(9)(10)(11)(12)(13)(14)(15). In Neurologie, Notfall-und Intensivmedizin wird die transorbitale Sonografie zunehmend eingesetzt, unter anderem für die Abklärung eines erhöhten intrakraniellen Drucks [10].…”
Section: Transorbitale Sonografieunclassified